2013
DOI: 10.1016/j.ymgme.2013.01.021
|View full text |Cite
|
Sign up to set email alerts
|

The Morquio A Clinical Assessment Program: Baseline results illustrating progressive, multisystemic clinical impairments in Morquio A subjects

Abstract: MPS IVA is a multisystem disorder with a continuum of clinical presentation. All affected individuals experience significant functional limitations and reduced quality of life. Older patients have more severe exercise and respiratory capacity limitations, and more frequent cardiac pathology illustrating the progressive nature of disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

12
229
1
5

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

5
2

Authors

Journals

citations
Cited by 129 publications
(249 citation statements)
references
References 40 publications
12
229
1
5
Order By: Relevance
“…The 6MWT is a multi‐systemic test, though improvement may not be demonstrated in this endpoint in each individual benefiting from treatment due to the heterogeneity of the disease and variable impact of ERT on outcomes. Results of the 3MSCT also showed that patients in this study had a relatively high level of function, with the number of stairs climbed per minute at baseline being more than twice that seen in the phase 3 and MorCAP studies [Harmatz et al, 2013; Hendriksz et al, [Link]]. After 24 weeks of treatment, the 3MSCT showed a numerical improvement at the higher dose, but not at the lower dose, though there was a high degree of variability at both baseline and outcomes among subjects for this test.…”
Section: Discussionsupporting
confidence: 61%
See 2 more Smart Citations
“…The 6MWT is a multi‐systemic test, though improvement may not be demonstrated in this endpoint in each individual benefiting from treatment due to the heterogeneity of the disease and variable impact of ERT on outcomes. Results of the 3MSCT also showed that patients in this study had a relatively high level of function, with the number of stairs climbed per minute at baseline being more than twice that seen in the phase 3 and MorCAP studies [Harmatz et al, 2013; Hendriksz et al, [Link]]. After 24 weeks of treatment, the 3MSCT showed a numerical improvement at the higher dose, but not at the lower dose, though there was a high degree of variability at both baseline and outcomes among subjects for this test.…”
Section: Discussionsupporting
confidence: 61%
“…Moreover, as previously indicated, the study was not powered to detect significant differences between doses. uKS has been suggested to be a biomarker of clinical severity in Morquio A syndrome [Harmatz et al, 2013], but no clear link between treatment‐induced uKS changes and clinical efficacy could be established in clinical studies thus far.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mucopolysaccharidoses IV A, better known as Morquio-A syndrome, is a rare disease that represents one of the multi-organic and progressive diseases with the most severe musculoskeletal system involvement (1,2). It has a wide clinical spectrum, that may not be easy to recognize from other non-systemic skeletal dysplasias, which represents a challenge in diagnosis in young patients (3,4).…”
Section: Introductionmentioning
confidence: 99%
“…Patients with a classic (severe) form of MPS IVA have a unique systemic skeletal dysplasia including short-trunk dwarfism, kyphoscoliosis, coxa valga, odontoid hypoplasia, abnormal gait, joint mobility problems, restriction of chest wall movement, and a life span of 20-30 years if an appropriate orthopedic intervention is unavailable. Patients with an attenuated form have a milder skeletal involvement, and most have normal life span (Dũng et al 2013;Yasuda et al 2013;Tomatsu et al 2011Tomatsu et al , 2012aTomatsu et al , 2013aNorthover et al 1996;Montaño et al 2007Montaño et al , 2008Suzuki et al 2001;Hendriksz et al 2013;M€ ollmann et al 2013;Harmatz et al 2013). Patients with MPS IVB show a milder phenotype of skeletal dysplasia than patients with the severe form of MPS IVA.…”
Section: Introductionmentioning
confidence: 99%